Carlos Fuentes: Pohřbené zrcadlo.: ze španělského originálu El espejo enterrado, México, D. F.: Fondo de Cultura Económica, 1992, přeložila Anna Tkáčová, Praha, Mladá fronta, 2003 - Halbich, Marek (Lidé města, 2006)
A review of the book by Carlos Fuentes.